Disentangling the effect of seed size and crystal habit on gold nanoparticle seeded growth. Issue 82 (3rd October 2017) - González-Rubio, Guillermo; de Oliveira, Thais Milagres; Altantzis, Thomas; La Porta, Andrea; Guerrero-Martínez, Andrés; Bals, Sara; Scarabelli, Leonardo; Liz-Marzán, Luis. M.
Abstract : Oxidative etching was used to produce gold seeds of different sizes and crystal habits. Abstract : Oxidative etching was used to produce gold seeds of different sizes and crystal habits. Following detailed characterization, the seeds were grown under different conditions. Our results bring new insights toward understanding the effect of size and crystallinity on the growth of anisotropic particles, whilst identifying guidelines for the optimisation of new synthetic protocols of predesigned seeds.